2015
DOI: 10.3109/1061186x.2015.1015536
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR-133a and miR-326 in ADM resistance of HepG2 through modulating expression of ABCC1

Abstract: Recent studies have shown that a class of small, functional RNAs, named microRNAs, may regulate multidrug resistance-associated protein 1 (ABCC1). Since ABCC1 is an important efflux transporter responsible for cellular drug disposition, the discovery of microRNAs (miRNA) brings an idea that there may be some other unknown multidrug resistance (MDR) mechanisms exist. Using computational programs, we predicted that the 3'untranslated region (3'UTR) of ABCC1 contains a potential miRNA binding site for miR-133a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Recently, growing pieces of evidence have shown that miR-133a acts as a tumor suppressor in prostate cancer [17], bladder cancer [18], head and neck cancer [19], esophageal cancer [20], and colorectal cancer [21], suggesting that miR-133a may serve as a potential therapeutic gene for the treatment of these cancers. Although a recent study has demonstrated that miR-133a could regulate multidrug resistance mediated by targeting multidrugresistance-associated protein 1 (ABCC1) in HCC cell line HepG2 [22], the clinical importance of miR-133a in HCC progression, the detailed function, and underlying molecular mechanism of miR-133a in HCC have not yet been thoroughly validated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, growing pieces of evidence have shown that miR-133a acts as a tumor suppressor in prostate cancer [17], bladder cancer [18], head and neck cancer [19], esophageal cancer [20], and colorectal cancer [21], suggesting that miR-133a may serve as a potential therapeutic gene for the treatment of these cancers. Although a recent study has demonstrated that miR-133a could regulate multidrug resistance mediated by targeting multidrugresistance-associated protein 1 (ABCC1) in HCC cell line HepG2 [22], the clinical importance of miR-133a in HCC progression, the detailed function, and underlying molecular mechanism of miR-133a in HCC have not yet been thoroughly validated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that dys-regulation of miRNAs plays a vital role in regulating the drug response of tumor cells [8,[30][31][32]. For instance, miR-133a and miR-326 are involved in adriamycin resistance in HepG2 cells through altering expression of multidrug resistance-associated protein 1 (ABCC1) [33]. Moreover, p53 suppresses miR-520 g expression, which mediates drug resistance through down-regulation of p21 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that miR-326 directly acted on the 39UTR of ABCC1, reduced ABCC1 mRNA and protein expression, and sensitized drug-resistant MCF-7 cells to chemotherapy (Liang et al, 2010). Other ABCC1 regulatory miRNAs evaluated by biologic experiments include miR-134 and miR-7 in small cell lung cancer cells (Guo et al, 2010;Liu et al, 2015), miR-1291 in pancreatic cancer cells (Pan et al, 2013), and miR-133a in hepatocarcinoma cells (Ma et al, 2015). Likewise, restoring the expression or function of such ABCC1 regulatory miRNAs increased intracellular drug accumulation and chemosensitivity, supporting the feasibility of miRNA-based strategies to improve therapy (Fig.…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%